2017
DOI: 10.1007/s11115-017-0381-7
|View full text |Cite
|
Sign up to set email alerts
|

Productive Resistance within the Korean Public Sector: Exploring Organisational Culture

Abstract: The article examines how South Korean civil servants responded to the introduction of pay for performance. Drawing upon 31 in-depth interviews with career civil servants, it identifies what became known as 1/n, a form of 'discreet resistance' that emerged and evolved. The analytical framework allows productive resistance to be seen as ebbing and flowing during organisational change that sees institutionalisation, deinstitutionalisation and re-institutionalisation. In understanding the cultural context of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…When it comes to the JD-R model, we also confirmed that transformational leadership is one of the important job resources that can positively affect employees’ attitudes and behaviors (Kim et al , 2018a, 2018b). Particularly, the findings of this study indicated that a transformational leader’ behaviors were considered as supportive job resources for employees in Korean organizations where they put more emphasis on the relationship between leaders and members (Park and Lunt, 2018; Park et al , 2017). Interdependency between leaders and members may result in positive and significant relationships between leadership and employee outcomes in our structural model.…”
Section: Discussionmentioning
confidence: 80%
“…When it comes to the JD-R model, we also confirmed that transformational leadership is one of the important job resources that can positively affect employees’ attitudes and behaviors (Kim et al , 2018a, 2018b). Particularly, the findings of this study indicated that a transformational leader’ behaviors were considered as supportive job resources for employees in Korean organizations where they put more emphasis on the relationship between leaders and members (Park and Lunt, 2018; Park et al , 2017). Interdependency between leaders and members may result in positive and significant relationships between leadership and employee outcomes in our structural model.…”
Section: Discussionmentioning
confidence: 80%
“…This result supports the idea that Anglo-American-style NPM reform cannot be a onesize-fits-all solution (Ho, De Jong, & Zhao, 2019), especially in East Asian culture. Many previous studies have raised the issue of Confucian culture in the expansion of the NPM doctrines in the East Asian context (Im, 2014;Park & Lunt, 2018;Park& Joo, 2010;Boo, 2010). The second interesting result is that there is a significant difference between the customer and partner groups regarding expectations and satisfaction with respect to the quality of maintained living area but not regarding performance.…”
Section: Discussion: Implications and Limitationsmentioning
confidence: 99%
“…Exploring its impactful outcomes, resistance was claimed to be potentially efficacious for management in promoting organizational change (Ford, Ford, & D’Amelio, 2008; McDermott, Fitzgerald, & Buchanan, 2013). For example, ‘facilitative resistance’ was argued to enable organizational change processes based on the transformation of knowledge (Thomas & Hardy, 2011) or on strong networks of relations and reciprocity (Park & Lunt, 2018). Thus, rather than a hindrance to change, resistance was integrated into organizational change processes, thereby enhancing the organization (Erwin & Garman, 2010).…”
Section: Productive Resistance and Changementioning
confidence: 99%